Incidence rate of positive HIV discovered in pre-operatively tests at AL-Yarmouk Teaching Hospital during 2020 to 2024 - K. Jameel, Sarab; A. Abdulrazzaq, Russell; K. AL-Taiem, Oruba; H. Mahmood, Israa; H. Hayyawi, Ali; M. Idrees, Inas (Journal of Neonatal Surgery, 2025)
Abstract Background: Human immunodeficiency virus (HIV) has resulted in 40.1 million fatalities worldwide; it may cause acquired immunodeficiency syndrome (AIDS). Its commonly transmitted to susceptible individuals especially health workers by several procedures, including transfusion of blood and its products; various surgical procedures; dialysis etc., the probability of male-to-female transmission HIV sexually is usually higher than the vice versa. Happening of HIV infection in the whole age groups, however, in males over 40 and below, while in females over 40-year-old only. HIV has been found in each Arab state and these prevalence of virus as a result of heterosexual relationship and/or drug injection. Some independent factors could associate with HIV prevalence like: season, climate and residence. Methods: present study was conducted on total (75,702) pre-operative(pre-surgical) blood sample were collected from both genders (38,681 male, 37,021female) with all age groups, were referred to the Department of Teaching Laboratories in AL-Yarmouk Teaching Hospital at Baghdad / Iraq, as a part of procedures of laboratories tests, which covered a period of five years from January2020 to December 2024. The laboratory testing method was Enzyme Linked Immunosorbent Assay (ELISA) BioTek /REF (50TS8) -USA, to detect HIV Ab-Ag in serum specimens. Results: from 75,702 total blood samples ,HIV infection was 39(0.05%) patients during 5 study years , 35 males (89.7%) and 4 females (10.2%), the highest rate of HIV infection of pre-operative patients was equally in 2024 and 2022(12/16307) and (12/13884) respectively, and the age ranged between 18-50 years old , when recorded highest percentage of HIV incidence in age group 30-49(53.8%), also high percentage of HIV infection (P-value = 0.574) in (Summer and Autumn) seasons (61.5%) when comparable with (Winter & Spring) seasons results (38.5%). Conclusion: The incidence of HIV in Baghdad during the five years of this study was low 39 (0.05%) from75,702 patients, and the incidence of HIV infection wasn’t significantly influenced with factors like: seasonal climate (seasons of the year), age and gender. It’s necessary to include a screening HIV as laboratory test within the ordinary tests to all patients, to protect the health workers, and confirmation to use the Personal Protective Equipment (PPE) and attempt to evolve and support vaccine programs to apply it on the community and increased consciousness of the risks and methods of transmission of HIV especially in adolescents and adult’s category with confirmed to use a combination drug of HIV to allows the immune system to repair itself and prevent further damage